Computing Concepts with Java Essentials - Horstmann, Cay S., 1959- (New York : John Wiley & Son, Inc, 2003)
* Features the most effective introduction to computing and programming, using the most current version of the Java language (Java 1.4) * Includes expanded coverage of Applets and Graphics * The new edition features a stronger emphasis on design and interesting Java features * Material points out common mistakes, so that the reader will know to avoid them Wiley Higher Education.
Includes Index
Keywords: Electronic data processing; Java (Computer program language)